2017
DOI: 10.18632/oncotarget.17281
|View full text |Cite
|
Sign up to set email alerts
|

Api5 a new cofactor of estrogen receptor alpha involved in breast cancer outcome

Abstract: Api5 (Apoptosis inhibitor 5) is an anti-apoptotic factor that confers resistance to genotoxic stress in human cancer. Api5 is also expressed in endothelial cells and participates to the Estrogen Receptor α (ERα) signaling to promote cell migration. In this study, we found an over expression of Api5 in human breast cancer. Given that we show that high expression of Api5 in breast cancer patients is associated with shorter recurrence free survival, we investigated the relationship between ERα and Api5 at the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…As a ligand of TLR4, apoptosis inhibitor 5 (API5) is an apoptosis inhibitory protein that prevents apoptosis induced by the transcription factor E2F1 and interacts with a nuclear factor involved in apoptotic DNA fragmentation 55 57 . For instance, API5 is associated with diseases, including adenocarcinoma and cervical cancer 58 , 59 . It can be released from tumor cells and functions as a DAMP protein activating immune cells 57 .…”
Section: Damp Proteins Released From Dying Cellsmentioning
confidence: 99%
“…As a ligand of TLR4, apoptosis inhibitor 5 (API5) is an apoptosis inhibitory protein that prevents apoptosis induced by the transcription factor E2F1 and interacts with a nuclear factor involved in apoptotic DNA fragmentation 55 57 . For instance, API5 is associated with diseases, including adenocarcinoma and cervical cancer 58 , 59 . It can be released from tumor cells and functions as a DAMP protein activating immune cells 57 .…”
Section: Damp Proteins Released From Dying Cellsmentioning
confidence: 99%
“…Triple-negative breast cancer is highly malignant, aggressive, resistant to chemotherapy, and has a poor prognosis[ 3 5 ]. However, the molecular mechanisms of breast cancer remain unclear[ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced and low levels of Api5 are associated with the increase in cell death in various cancers. Knockdown of Api5 resulted in the reduction in in vivo tumorogenicity in cancer cells 14 .…”
Section: Introductionmentioning
confidence: 99%
“…High levels of Api5 provide cancer cells the ability to evade immune response mediated cell death 6 . In breast cancers, Api5 interacts with the estrogen receptor to promote proliferation 14 . It has also been reported that Api5 promotes metastasis in breast cancers 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation